A long hole stoping system for mining narrow platinum reefs - P. van Dorssen; P. Valicek; M. Farren; G. Harrison; W. Joubert; R. G. B. Pickering; H. J. van Rensburg (The Southern African Institute of Mining and Metallurgy, 2001)
Introduction In South African metalliferous mines, stoping operations are largely confined to narrow, tabular orebodies making mechanization extremely difficult. Limited flexibility in terms of stope width has necessitated drilling by means of hand held, pneumatic rock drills at most of our operations. As the largest producer of platinum in the world, we drill in excess of forty million stope blast holes per annum. Cleaning of the broken ore is also done by conventional means—utilizing scrapers and scraper winches. Conventional methods such as these carry high costs in terms of risk exposure as well as labour intensity. The purpose of this paper is to describe the development of a long hole stoping system suitable for the narrow platinum reefs. The new system had to be substantially safer and more cost effective than conventional mining. We selected a site that was conducive to mechanized mining and set out the parameters that we considered would meet our requirements. We then conducted a feasibility study to evaluate the conceptualized long hole stoping system in terms of specific goals. An analysis of the proposed system identified the Key Performance Indicators (KPIs). One of the most critical goals was to be able to create a man-freestope. This would mitigate the safety risk associated with normal stoping operations, as well as the inefficiency cost previously referred to. Other challenges included setting targets for long hole accuracy, stoping width reduction and specific blasting system performance for long hole stoping. We also modelled a critical span that we considered to be inherently safe and to ensure hangingwall stability, throw-blastcleaning and overall system productivity. Anglo Platinum Research and Development and Sandvik Tamrock entered into an agreement for the supply of a specialized long hole-drilling machine. The system was implemented and tested by the mine with the support of the other participants. The results achieved met our expectations. It was demonstrated that with this method of mining it is possible to have a man-free/support-free stope face and to achieve a reduction in shaft head cost per ton whilst reducing dilution. Key performance indicators assessed during the trial •Safety targets •Mining layout •Drill rig •Production targets •Support requirement •Explosives requirement •Services requirement •Ore removal and cleaning requirement •Training requirement Safety targets All persons involved with the project had to adhere to the mine’s safety programme including the zero-tolerance campaign, and were required to report all hazards observed immediately. Mine personnel and Tamrock carried out a full risk assessment on the drill rig before transporting underground. A further risk assessment was carried out when the machine was in position underground. Mining layout See Figure 1 and Figure 2 for a detailed description. Drill rig The drill rig was a combination of a Secoma P-Low LC 10long hole feed and an Axera low profile carrier. The choice of this equipment was made through consultation with Tamrock Sandvik. All relevant design perimeters of the area to be mined were taken into consideration. Production targets